Accentuating and Opposing Factors Leading to Development of Thoracic Aortic Aneurysms Not Due to Genetic or Inherited Conditions - Rabkin, Simon W. (Frontiers in Cardiovascular Medicine, 2015)
Understanding and unraveling the pathophysiology of thoracic aortic aneurysm (TAA), a vascular disease with a potentially high mortality rate, is one of the next frontiers in vascular biology. The processes leading to the formation of TAA that are not of known or suspected genetic origin, so-called degenerative TAA, are complex, interwoven and involve promoters and inhibitors at many potential sites. Some of these processes are discussed within this framework. Promoters of TAA development include age, blood pressure elevation, increased pulse pressure, neurohumeral factors increasing blood pressure, inflammation specifically IFN-γ, IL-1 β, IL-6, TNF-α and S100 A12; the coagulation system specifically plasmin, platelets and thrombin as well as matrix metalloproteinases (MMPs). Aortic calcification mechanisms and SMAD-2 signaling also promotes TAA development. The major factors inhibiting or opposing TAA development are the constituents of the aortic wall (elastic lamellae, collagen, fibulins, fibronectin, proteoglycans and vascular smooth muscle cells) which maintain normal aortic dimensions in the face of aortic wall stress. Inhibitors of MMP, specific tissue inhibitors of metalloproteinases (TIMPs), plasminogen activator inhibitor-1, protease nexin-1 and Syndecans act to oppose TAA formation. Increases in promoters and reductions in inhibitors expand the thoracic aorta leading to TAA formation.